Innovative leadership of secondary school administrators: A case study of pilot schools of education sandbox - Sungtong, Ekkarin; Thupaang, Anupap; Ponlawat, Attapon (LPMPP Universitas Negeri Yogyakarta, 2025)
The objectives of this research were to (1) study the innovative leadership of secondary school administrators and (2) examine the challenges in developing innovations within the pilot schools of the education sandbox in Krabi, Thailand. The key informants included six school administrators and six teachers responsible for innovation tasks, totalling 12 participants selected through purposive sampling. A semi-structured interview protocol was used, and data were analyzed using thematic network analysis, with trustworthiness established through rapport building with participants. The findings indicate that the innovative leadership of secondary school administrators in Krabi encompasses four main aspects: (1) Vision for change, which entails establishing a clear direction for innovation; (2) Innovative organization atmosphere, which centers on creating a supportive environment for innovation; (3) Utilizing information and communication technology, which underscores the use of modern tools to enhance communication; and (4) Fostering collaboration, which involves promoting teamwork and partnerships. The challenges in developing innovations include issues related to (1) personnel, such as communication problems, misunderstandings among staff, and frequent turnover; (2) students, including economic status, incomplete family situations, and academic achievement; (3) budget, with insufficient funds; and (4) community, involving community values and support.